Clinical characteristics and management of primary retroperitoneal sarcoma: A literature review - Yukinori Yamagata; Motokiyo Komiyama; Shintaro Iwata (Annals of Gastroenterological Surgery, 2024)
Abstract Retroperitoneal sarcoma (RPS) is a rare tumor classified into many histological types. It is also often detected only after it has grown to a considerable size and requires extensive resection of the surrounding organs, making it difficult to offer optimal patient‐tailored management. Evidence supporting specific treatment modalities for RPS is insufficient, owing to its rarity. The Japanese clinical practice guidelines for RPS were published in December 2021, with the aim of accumulating existing evidence and indicating the optimal practice for RPS. These guidelines provide important clinical questions (CQs) concerning the diagnosis and treatment of RPS. This review, with a particular focus on primary RPS, attempts to introduce clinical problems in the diagnosis and treatment of RPS and to assess those problems along with the CQs in the guidelines. According to these guidelines, although chemotherapy and radiotherapy are expected to have therapeutic effects, the level of evidence to support these treatments is not very high at present. Accordingly, complete resection of the tumor is the first and only option for managing primary RPS. However, as with other tumors, the demand for multidisciplinary treatment for RPS is increasing. These guidelines will undoubtedly represent a milestone in clinical practice in relation to RPS in the future, and further evidence is expected to be accumulated based on the CQs that have been proposed.